SHALE REVOLUTION AND THE COMPETITIVENESS OF U.S. INDUSTRY - A. Yu. Mishin (Модернизация, инновация, развитие)
The publication is devoted to the impact of shale gas revolution on the competitiveness ofU.S.industry. The author examines the shale revolution as a tool to improve competitiveness ofU.S.industry. The analysis of available publications and different opinions on this issue, given the impact factor model ofU.S.energy policy on the competitiveness of products and calculated generalized economic evaluation of cost share of natural gas in the value of industrial production, conclusions.